Use and access possibilities in the field of training future drivers using a vehicle simulator - Libor Topol (Acta Polytechnica CTU Proceedings, 2024)
Novice drivers between the ages of 18 and 24 have a higher risk of accidents, which results from long-term published statistical data. The goal of training at driving schools should be the comprehensive preparation of future drivers for all traffic situations under various weather conditions. Using vehicle simulators allows this practice and training of future drivers, which can be fulfilled and practiced in all weather conditions. Moreover, the vehicle simulator practice can be subsequently (machine) evaluated. Based on the analysis of such driving, complex erudition and readiness of the future driver behavior in real road traffic can be achieved. This article discusses the capabilities of simulator software that can be applied to the education and training of future drivers. The article aims to present possibilities of evaluation software and related practical use in driver education in driving schools. At the end of the article, the expected benefits in the design of the evaluation software for the vehicle simulator are discussed, emphasizing road safety in the education of future drivers.